The butcher, the brewer, or the baker: The role of occupations in explaining wage inequality - Hou, S; Milsom, L (University of Oxford, 2021)
Google does not pay its canteen chefs the same premium as it does its software engineers; there is heterogeneity in pay premia within a firm. To study the implications of this observation, we estimate a two-way, worker-job, fixed effect model that builds upon the canonical model by Abowd et al. (1999) by allowing for within-firm heterogeneity. Estimating our model on UK administrative data, we find that even if workers, and firms, were identical, 25% of current log-wage variance would remain, due solely to heterogeneity between occupations. We further document that worker heterogeneity accounts for a relatively small proportion of log-wage variance, and that between-firm pay heterogeneity is more important in higher-wage occupations and larger labour markets.